ARTIFICIAL INTELLIGENCE AND AUTOMATION: AN ANALYSIS OF THE LITERATURE ON INNOVATION AND PRODUCTIVITY - Loso Judijanto; Hadenan Towpek (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
This article analyses the existing literature on the impact of artificial intelligence (AI) and automation on innovation and productivity. With the increasing adoption of these technologies across sectors, there has been a significant shift in the way business operations and strategies are conducted to achieve higher efficiency and develop new products and services. On the other hand, the article also highlights the challenges that need to be overcome, including potential disruptions in the labour market and the need for retraining of the workforce. Through comprehensive analysis, the paper offers insights into how AI and automation can be maximised to drive economic growth while ensuring social welfare.